2021
DOI: 10.3390/diagnostics11112068
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of an Ongoing Prospective Clinical Trial on the Use of 68Ga-PSMA and 68Ga-DOTA-RM2 PET/MRI in Staging of High-Risk Prostate Cancer Patients

Abstract: The aim of the present study is to investigate the synergic role of 68Ga-PSMA PET/MRI and 68Ga-DOTA-RM2 PET/MRI in prostate cancer (PCa) staging. We present pilot data on twenty-two patients with biopsy-proven PCa that underwent 68Ga-PSMA PET/MRI for staging purposes, with 19/22 also undergoing 68Gaa-DOTA-RM2 PET/MRI. TNM classification based on image findings was performed and quantitative imaging parameters were collected for each scan. Furthermore, twelve patients underwent radical prostatectomy with the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…So far, only few studies have investigated the combined use of both 68 Ga-PSMA and 68 Ga-DOTA-RM2 PET in PCa both in the staging and restaging setting, using PET/MRI and PET/CT alternatively [ 10 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, only few studies have investigated the combined use of both 68 Ga-PSMA and 68 Ga-DOTA-RM2 PET in PCa both in the staging and restaging setting, using PET/MRI and PET/CT alternatively [ 10 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, GRPR analogues have been recently identified as alterative targets for molecular imaging in prostate cancer [ 8 ]. So far, among the available radiotracers targeting GRPR, 68 Ga-DOTA-RM2 has been the most investigated [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent preclinical study, which evaluated retrospectively frozen prostatectomy samples ( n = 20) with tissular microimaging using [ 111 In]In-PSMA-617 and the GRPr antagonist [ 111 In]In-RM2 ([ 111 In]In-DOTA-4-amino-1-carboxymethyl-piperidine- D -Phe 6 -Gln 7 -Trp 8 -Ala 9 -Val 10 -Gly 11 -His 12 -Sta 13 -Leu 14 -NH 2 ), showed that for [ 111 In]In-PSMA-617 the binding was high and independent of the metastatic risk ( p = 0.665), Gleason score ( p = 0.555), or PSA value ( p = 0.404), while [ 111 In]In-RM2 exhibited a significantly higher binding in the low metastatic risk group ( p = 0.046), in the low PSA value group ( p = 0.001), and in samples with Gleason 6 score ( p = 0.006) [ 162 ]. A limited number of patients have been screened with a PSMA-targeting imaging agent ([ 68 Ga]Ga-PSMA-11 or [ 18 F]DCFPyL) and the GRPr antagonist [ 68 Ga]Ga-RM2 [ 163 , 164 , 165 , 166 , 167 ] resulting rather in a complementing than in a competing approach of PSMA vs. GRPr imaging [ 165 , 168 ].…”
Section: Multitargeted Psma Inhibitorsmentioning
confidence: 99%